Analysis of Language Acquisition in Early Children's Language Development and Teaching - Herawati Parapat, Lili; Riskiana Aritonang, Devinna; Lubis, Khatib; Rahmad Daulay, Ismail; ., Rosmaimuna (KnE Social Sciences, 2023)
The research objective was to identify and describe the results of the analysis of language acquisition in the development and preparation of early childhood language in Paringgonan village as phonology teaching materials. The method used is descriptive method. Collecting data using observation, taking notes in the form of records, important notes from interviews. Data analysis techniques used are reduction, presentation, and retrieval of research results. Based on the research results, it is known that the language stimuli received by children are regular. Children understand understand linguistic systems of first language before turning 5 years of age. However, after coaching and building good and correct language for children. It is known that 78% of children’s language acquisition is better in pronouncing vowels, consonants, every word & sentence (in the field of phonology) using Indonesian. Furthermore, based on the results of interviews with the child’s parents, it is known that 80% of the educational background & application of the parents greatly affects the child’s language in good and correct language. Keywords: Language acquisition; development; early children’s; teaching